(untitled) (Research, Society and Development, 2023)
Objective: To validate and introduce a method for assessing competencies in Pediatrics for residents of the Medical Residency Program in Pediatrics of a Public Health Institution in the Amazon. Methods: This is a cross-sectional and analytical study with a quali-quantitative approach with teachers, preceptors, pediatrics residents, nurses and patients’ families in three sectors of the Pediatrics Medical Residency Program, between April and July 2018. Results: The instruments were validated by seven judges with an average of 15 years in the teaching profession; 139 evaluations were obtained from 26 residents, mostly women (80.8%) and first year of training (R1); 33.8% by teachers/preceptors and nurses (Mini-CEX instrument), 38.2% by family members and 28% by residents through self- and/or peer evaluation. For feedback, there was no record in the mini-CEX and, among family members, there was a predominance of compliments, as well as in self/peer evaluations. Better evaluations occurred by peers regarding self-assessments on the topics: psychosocial aspects of the disease and medical knowledge (R1); and management in outpatient care, management of multiple complex problems, and management of hospitalized patients (R2). In the assessment of family members, the R2 scored higher in two items than the R1: talks all about his disease; as for the miniCEX, the R2 performed better in clinical skills, clinical reasoning, anamnesis and physical examination. Reliability in the three instruments, with Cronbach’s alpha coefficient: self/peers assessment (0.72), miniCex (0.9) and family members’ assessment (0.86). Conclusion: Use of the method allowed qualities to be observed in the individual and collective context of this group of professionals.